Efeito da fertirrigação com potássio sobre o solo e produtividade do morangueiro - Gomes, Edilson Ramos [UNESP]; Broetto, Fernando [UNESP]; Queluz, João Gabriel Thomaz [UNESP]; Bressan, Dayanne Fabrício [UNESP] (My University, 2015)
Proper irrigation management associated with appropriate plant nutrition leads to higher yield gain and better physiochemical properties of the fruit. The objective of this study was to evaluate the effect of fertigation with different irrigation levels and distinct concentrations of potassium on soil and strawberry yield. The experiment was conducted in a greenhouse and strawberries were grown in beds. The treatments were arranged in a randomized split-plot experimental design with four replicates. Treatments consisted of five irrigation levels (125%, 100%, 75%, 50% and 25% water requirement of the crop) and three doses of potassium fertilization applied to the subplots (0, 300 and 900 kg ha-1 cycle-1). Potassium fertigation increased electrical conductivity and reduced pH in the soil solution. The ion effect promoted by potassium as a function of water regimes affected the strawberry yield and the physiochemical characteristics of fruits. The recommended dose of potassium to the strawberry in association with water applied in excess promote higher crop yield.
Effect of potassium fertigation on soil and strawberry yield
Keywords: Fertigation; Fragaria L; Soil solution extractor